Portugal : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This paper reviews economic developments in Portugal-Macau during 1997-99. It highlights the way in which Macau's economic development evolved over the years. The paper discusses developments in prices, wages, and employment, and sheds light on how the product and labor markets adjusted to external shocks-in particular to the Asian crisis as well as the increased competition faced by the economy in recent years (1997-99). The paper also reviews the budgetary process and budgetary developments and highlights structural problems that are inherent in the fiscal system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet